Observer design for system with variable measurement sampling rate - Wang, Jianxin. (2008)
In this dissertation, the observer design problems for systems with variable measurement sampling-rates are discussed. Systems with variable measurement sampling-rates are encountered in situations when position information is embedded along the actual trajectories. In this case, measurements are available only when the system comes across a sensor mark. The fact that the sampling period is variable makes it hard to draw conclusions on the system behavior. In this dissertation, an expression for the observer error dynamics is derived. The structure of the error dynamics shows that proper design of the observer gain is important. Furthermore, sufficient conditions for error convergence are derived, and two variable measurement sampling-rate observer design procedures are proposed. Simulation results demonstrate the effectiveness of the proposed approach.